PENGARUH MODIFIKASI PEMBELAJARAN DARING TERHADAP PENINGKATAN PENGETAHUAN IBU HAMIL KURANG ENERGI KRONIS (KEK) - Hartati, Hartati; Sumarni, Sumarni; Anonim, Tri (Jurnal Lintas Keperawatan, 2021)
Chronic energy deficiency is the state in which the pregnant women suffer the lack of food chronically (chronic). The effect of chronic energy deficiency causes death to the mother and fetus, the further impact of chronic energy deficiency can cause physical growth disorders (stunting), brain and metabolic disorders that make it susceptible to disease during the Covid 19 pandemic. This study aims to examine the effectiveness of online learning modifications about nutrition to increase the knowledge of chronic energy deficient pregnant women in South Pekalongan.The design of this research is an experimental quasi study with the Two group pretest-post test design. The research sample of 40 respondents consists of 20 respondents treatment groups and 20 respondents in the control groups. The intervention in the online learning treatment group, and the control group by learning to read the KIA book, was carried out for 15 days. Statistical test uses the Paried t test for the test for normally distributed data and uses Wilcoxon for abnormal data distribution.The statistical test result states that there is a difference in the knowledge of pregnant women in chronic energy deficiency (KEK) between those who are given modified online learning and learning through the KIA book with r: 0,000.Â Keyword: KEK, Learning, Online Learning